From infection to autoimmunity: can COVID-19 spark new auto-immune conditions? - Mourad Elghali; Mariem Mhiri; Imen Chaabene; Ines Bayar; Bilel Ben Amor; Imen Jaziri; Maha Changuel; Rihab Ben Dhia; Narjes Gouta; Jamel Saad; Rym Hadhri; Ahmed Zrig; et al. (Respiratory Medicine Case Reports)
Background: Some studies have described a probable relationship between SARS-CoV-2 infection and autoimmunity. Aim: to present a case series of autoimmune manifestations (AIM) following COVID-19 infection. Methods: A consecutive series of patients from January 2020 to December 2023 was collected from the various departments of Fattouma Bourguiba University Hospital, Monastir, where all clinical assessments were performed. Anti-nuclear antibody (ANA) screening was performed using indirect immunofluorescence on HEp-2 cells (Euroimmun, Germany) with a positivity titer of ≥1/180. Typing was performed using ELISA (Biosystems, Spain) or line blot (Euroimmun, Germany). The assessment of other autoantibodies was performed using various techniques (indirect immunofluorescence, ELISA, and line blot). Results: Sixteen patients presented with AIM after the COVID-19 infection. Their ages ranged from 12 to 67 years (44.6 ± 15.5 years). The sex ratio was 1 (eight men to eight women). Clinical manifestations began between one week and three months after infection. The clinical presentation was polymorphic (general, cutaneous, neurological, ophthalmic, muscular, articular, and abdominal features). Biological, radiological, and histopathological investigations revealed principal abnormalities in endocrine, articular, muscular, or neurological functions in the presence of ANA and/or specific autoantibodies. Fiveteen patients were diagnosed with autoimmune diseases (AID) and treated with specific treatments. The diagnosis retained for the other case was non-specific autoimmune stimulation with spontaneous recovery. Conclusion: These cases suggest that AID or AIM can be triggered or unmasked by SARS-CoV-2 infection.